2015
DOI: 10.1088/2041-8205/812/2/l29
|View full text |Cite
|
Sign up to set email alerts
|

The VVV Survey Reveals Classical Cepheids Tracing a Young and Thin Stellar Disk Across the Galaxy’s Bulge

Abstract: Solid insight into the physics of the inner Milky Way is key to understanding our Galaxy's evolution, but extreme dust obscuration has historically hindered efforts to map the area along the Galactic mid-plane. New comprehensive near-infrared time-series photometry from the VVV Survey has revealed 35 classical Cepheids, tracing a previously unobserved component of the inner Galaxy, namely a ubiquitous inner thin disk of young stars along the Galactic mid-plane, traversing across the bulge. The discovered perio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 42 publications
1
57
1
Order By: Relevance
“…These stars are formed in situ, and have high metallicity and low α-element enhancements; they formed from heavily recycled material. It would of great interest to measure the chemical abundances of the cepheids stars that have been detected in the bulge of the MW (Dékány et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These stars are formed in situ, and have high metallicity and low α-element enhancements; they formed from heavily recycled material. It would of great interest to measure the chemical abundances of the cepheids stars that have been detected in the bulge of the MW (Dékány et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of them are part of the bulge component (i.e., they belong to the most gravitationallybound stellar populations). Recent discoveries of cepheids in the bulge of the MW indicates the existence of young stars in the bulge (Dékány et al 2015). A census of these young populations would be of utmost importance to set constraints on the formation of the MW and large spirals in general.…”
Section: Old Stars Within the Inner 10 Kpcmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the inner Galactic disk between the NSD and R ∼ 2 kpc is not well-known due to heavy extinction and crowding. Observations of maser stars and vvv Cepheids indicate a barred disk of young stars (Habing et al 2006;Dékány et al 2015). The cold kinematics of young bar stars has likely been seen in apogee LOS velocity histograms .…”
Section: The Galactic B/p Bulgementioning
confidence: 97%
“…Large numbers of RR Lyrae stars found in the ogle and vvv bulge surveys have shown that the most metal-poor ([Fe/H] = −1.0 ± 0.2), old population does not participate in the b/p-bulge (Dékány et al 2013;Pietrukowicz et al 2015), consistent with the argos result that only stars with [Fe/H] > ∼ − 0.5 participate in the split red clump (Ness et al 2012). The RR Lyrae stars show no significant rotation (Kunder et al 2016).…”
Section: Does the Milkymentioning
confidence: 99%